Forecasting of MRT Railway Rail Lifetime on Fatmawati Curve Jakarta-Indonesia - Najendra, Gifarly; Aghastya, Adya; Nurhadi, Muhammad (Nusantara Publisher, 2024)
This research analyzes the service life of rails on rail replacement on urban railway arches, with a focus on the Fatmawati MRT Jakarta arch. Due to the high frequency of train traffic in urban areas and curve radii that do not comply with standards, the rails on the Fatmawati curve experience significant wear. This research uses the AREA method to estimate the service life of rails based on the wear that occurs. The data collected includes the number of daily train trips and regular measurements of track wear. Analysis results show that rail wear on the Fatmawati curve is increasing, reaching a critical point in April 2029, where the rails are projected to have to be replaced. Using forecasting methods square train and least square, it is predicted that by April 2029, the numberof daily trips will decrease to 239 trips, and rail wear will reach 15.85 mm. This research provides recommendations for rail replacements to be carried out in accordance with predicted results to avoid further damage and maintain the operational safety of MRT Jakarta.